IMPLEMENTASI METODE WEIGHTED PRODUCT UNTUK PEMBERIAN BONUS KARYAWAN - Subekti, Dayat; Wicaksono, Arief Ikhwan; Mukti, Agung Permana; Azzuhry, Dimas Rully (University of Muhammadiyah Tangerang, 2024)
Giving bonuses to workers is an accomplishment that goes above and beyond the goal; it can raise productivity levels across the board for those involved. Employees frequently complain to business owners about differences in bonus calculations; these inaccuracies are frequently the result of incomplete data that was used to calculate and record data. The goal of this research is to apply the weighted product method algorithm to the decision support system for employee bonus distribution in order to promptly solve difficulties that arise. The MYSQL database, Django Framework, and Python programming language were used in the construction of the system. The weighted product method and the waterfall method are the two approaches used by the research road. The weighted product approach is used to determine bonuses, while the waterfall method is used for the phases of system development that include analysis, design, implementation, and testing. The study's findings will assist the finance department and business owners in organising data using preset criteria and performing calculations using the weighted product method to make employee bonus decisions easier.